2016
DOI: 10.4103/0976-7800.195698
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal obstruction associated with ovarian remnant in postmenopausal female

Abstract: Ovarian remnant syndrome (ORS) is a rare condition, in which the ovarian tissue is inadvertently left behind after difficult oophorectomy. The most common preexisting conditions associated for this complication include endometriosis, pelvic inflammatory disease, and prior abdominal surgery as in these conditions, removal of ovarian tissue becomes difficult. This is likely due to the presence of the dense fibrotic adhesions between an ovary and the surrounding structures. This residual ovarian tissue can become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Studies [ 3 ]have shown that replantation of ovarian specimens in the abdominal cavity can be viable even without blood supply in a cat model. Ectopic implantation of ovarian tissue has also been reported in cases of ORS after laparoscopic ovarian cyst excision, resulting in abdominal incision and intestinal obstruction [ 4 6 ]. Although rare, malignant tumors can develop from ovarian remnants, including mucinous cystadenocarcinoma, endometrioid adenocarcinoma, and borderline serous neoplasia [ 7 – 11 ], suggesting the possibility of malignant transformation of remnant ovarian tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Studies [ 3 ]have shown that replantation of ovarian specimens in the abdominal cavity can be viable even without blood supply in a cat model. Ectopic implantation of ovarian tissue has also been reported in cases of ORS after laparoscopic ovarian cyst excision, resulting in abdominal incision and intestinal obstruction [ 4 6 ]. Although rare, malignant tumors can develop from ovarian remnants, including mucinous cystadenocarcinoma, endometrioid adenocarcinoma, and borderline serous neoplasia [ 7 – 11 ], suggesting the possibility of malignant transformation of remnant ovarian tissue.…”
Section: Discussionmentioning
confidence: 99%